2004
DOI: 10.1262/jrd.50.297
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Tethered Equine Chorionic Gonadotropin (eCG) and Its Deglycosylated Mutants

Abstract: Abstract. Equine chorionic gonadotropin (eCG), which consists of highly glycosylated α-and β-subunits, is a unique member of the gonadotropin family because it elicits response characteristics of both follicle-stimulating hormone (FSH) and luteinizing hormone (LH) in species other than the horse. In this study, recombinant tethered-eCG as well as its deglycosylated mutants were produced to determine if α-and β-subunits can be synthesized as a single polypeptide chain (tethered-eCG) and display biological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(94 citation statements)
references
References 34 publications
7
87
0
Order By: Relevance
“…The cells were incubated at 37°C in 5% CO 2 . Cultured CHO-K1 cells were transfected with the expression vectors by using the liposome transfection method described previously [15]. Briefly, DNA (0.8 μg) was diluted in 50 μL of Opti-MEM I reduced medium without serum and mixed gently.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were incubated at 37°C in 5% CO 2 . Cultured CHO-K1 cells were transfected with the expression vectors by using the liposome transfection method described previously [15]. Briefly, DNA (0.8 μg) was diluted in 50 μL of Opti-MEM I reduced medium without serum and mixed gently.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, we can suppose that the three-dimensional conformation of single-chain eLH/CG could be altered when compared with heterodimeric eLH/CGs, as previously shown for hCG (Fralish et al 2003). Unlike previous studies which reported that eLH/CG b-a single chain was fully bioactive in vitro , Min et al 2004 and in vivo ( Jablonka-Shariff et al 2007), we report here that the b-a eLH/CG single-chain secretion by virus-infected insect cells was reduced when compared with heterodimeric eLH/CG and exhibited a slightly reduced in vitro LH bioactivity. Considering all these clues, it is of utmost interest to study the bioactivities of highly produced and fully bioactive heterodimeric glycoforms rather than those of single-chain variants whose conformation is potentially less similar to that of natural eCG and eLH.…”
Section: Discussionmentioning
confidence: 54%
“…The b-a configuration was widely used to produce recombinant single-chain glycoprotein hormones of many species (Narayan et al 1995, Boime & BenMenahem 1999, Dirnberger et al 2001, Fidler et al 2003, Min et al 2004, Jablonka-Shariff et al 2007, sometimes with heterologous CTP from hCG inserted between fused a-and b-subunits to enhance the secretion of these single-chain protein variants (Sugahara et al 1996, Garcia-Campayo et al 1997, Grossmann et al 1997, Fares et al 1998. These earlier studies showed that the CTP played the role of a flexible hydrophilic spacer allowing genetically fused a-and b-subunits to adopt a functional conformation and that secretion in the presence of CTP was enhanced due to its specific O-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…The correct plasmids were digested with Kpn I and Xho I, and then inserted into the same digested sites of the pGL3-Basic luciferase reporter vector (Promega, Madison, WI). Nucleotide inversion mutants (mut-1, mut-2, and mut-3) of the putative Ap-1 site were constructed according to the two-step overlapping PCR method [57] using the primers shown in Table 1. PCR was performed with Ex taq polymerase (TaKaRa, Osaka, Japan), and the mutant fragments were subcloned into the pCR 2.1.…”
Section: Methodsmentioning
confidence: 99%